"We'd Rather Be Relevant than Theoretically Accurate": The Translation and Commodification of Social Scientific Knowledge for Clinical Practice. (16th April 2020) - Olsen, Lauren D
Abstract: At the turn of the 21 st century, one of the ways in which the U.S. medical profession attempted to address the rampant health and healthcare disparities facing their patient populations was to pay more attention to a patient's culture . Proving to be easier said than done, the operationalization of the social scientific concept of culture for clinical practice has been fraught with implementation difficulties—from clinician buy-in to stereotyping. I draw upon ethnographic data to detail how an interdisciplinary group of social scientists and clinicians work to translate a theoretically-complex, reflexive, and social-justice-oriented conceptualization of culture into a clinical intervention tool. As opposed to previous accounts of interdisciplinary collaboration that describe social science being ignored, marginalized, or non-commodifiable, I show how this group makes the anthropological concept of culture both clinically and commercially relevant and the importance of clinicians-as-consumers in the translational process.